Teknik Sosiodrama Sebagai Upaya Peningkatan Perilaku Asertif Siswa - Nusantara, Boby Ardhian; Savira, Firda (Universitas Muria Kudus, 2024)
Assertive behavior has a positive impact, namely the desire for individual needs and feelings to be understood by others. In this way, no party is harmed because both parties feel appreciated and heard. The aim of this research is to determine the increase in assertive behavior through group guidance using sociodrama techniques. The research subjects were eight people. Data analysis used the Wilcoxon test statistics and the Friedman test. The research results showed an increase in assertive behavior through group guidance using sociodrama techniques. Future researchers are advised to conduct research on students' assertive behavior using different research methods. In addition, it can reveal specific aspects of students' assertive behavior. The results of the research, namely through the Wilcoxon test, showed that the hypothesis results in cycle I of increasing assertive behavior through group guidance using game based learning techniques were rejected or there was no increase (sig=0.735 p=0.05) and the hypothesis results in cycle II of increasing assertive behavior through group guidance using sociodrama techniques or an increase was accepted (sig=0.042 p=0.05). So it can be concluded that there is an increase in assertive behavior through the guidance of the sociodrama technique group.